Analysis of Digital Marketing Strategy Optimization to Enhance the Competitiveness of Food Sector MSMEs - Putri, Nia Rifanda; Cahyono, Ari Nugroho; Islamiyati, Dian (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study aims to analyze the influence of digital marketing strategies and optimization on the competitiveness of food sector MSMEs, as well as to examine the role of optimization as a moderating variable. The research employed a descriptive quantitative method with a sample of 101 respondents who are food sector MSME actors. Data were collected through questionnaires and analyzed using SPSS with classical assumption tests, multiple regression, F-test, t-test, and coefficient of determination (R²). The findings indicate that digital marketing strategies have a significant positive effect on MSME competitiveness, and optimization also significantly influences competitiveness. Furthermore, optimization moderates the relationship between digital marketing strategies and MSME competitiveness, where the effect of digital strategies becomes stronger when accompanied by effective business optimization. This study concludes that the combination of digital marketing strategies and optimization is a key factor in enhancing the competitiveness of food sector MSMEs.